ANALISIS KEBUTUHAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS BOT TELEGRAM MATERI PERSAMAAN DASAR AKUNTANSI PADA PEMBELAJARAN EKONOMI SMA - Septia, Septia; Purwaningsih, Endang; Kuswanti, Heni (Jurnal Edukasi Ekonomi, 2024)
The purpose of this study was to analyze the needs of learning media that support learning objectives by using interactive media based on bot Telegram on basic accounting equations in learning economics. The subjects in this study consisted of one economics teacher who taught in class XII IPS 1 and five students from the same class at SMA Negeri 11 Pontianak. The method used was descriptive qualitative research with a case study approach. The results showed that (1) basic accounting equation material is one of the basic materials that are difficult for students to understand; (2) students need interactive learning media that adopts technology, is interesting and innovative; (3) The use of Telegram bot-based learning media is considered the right solution to help achieve learning objectives on basic accounting equation material. Thus it is concluded that Telegram bot-based interactive learning media is needed in learning economics class XII SMA to facilitate teachers and students in the teaching and learning process.